ADHEAR in Conductive Hearing Loss: a case study. (24th June 2020) - Marques, T; Carvalho, A; Miguéis, A
Abstract: Introduction Bone conduction hearing systems can be applied through non-invasive devices, using soft bands that exert pressure on the skin, or they can be surgically implanted (Bone Anchored Hearing Aid - BAHA). However, these bone conduction devices are frequently not well accepted due to the pressure on the head. Therefore, a new non-surgical hearing system was developed not to exert pressure on the skin, the ADHEAR. The bone anchorage in ADHEAR is performed through an adhesive adapter and is indicated for patients with conductive hearing loss and normal inner ear function. Objectives Evaluate the audiological performance with the adhesive bone conduction hearing device (ADHEAR) in a patient with conductive hearing loss. Methodology The study was designed as a prospective single-subject repeated-measure study with the subject serving as his own control. A 29 year old female patient who had a primary surgery due to middle ear cholesteatoma, was adapted with unilateral non-invasive adhesive bone conduction system for the treatment of conductive hearing loss. Air and bone conduction thresholds, word recognition scores (WRS) and speech recognition thresholds (SRT) in quiet and noise were assessed to verify the inclusion criteria of the study. Aided and unaided pure tone audiometry at 0.5, 1, 2 and 4 kHz in free field and speech audiometry in quiet and noise were performed at baseline and after 4 weeks with the ADHEAR. Results The functional gain with the ADHEAR averaged over 0.5, 1, 2, and 4 kHz after 4 weeks of usage of the adhesive hearing system, improved from 55 dB HL to 31dB HL. Speech perception in quiet and noise improved significantly in the aided situation, with SRT in quiet improving from 60 to 35 dB HL, when compared to the unaided condition. Similar results were found in noise. The patient evaluated the ADHEAR system as being useful, and without complaints of skin pressure. There was no adverse skin reaction. Conclusion Hearing performance was significantly better with ADHEAR under all test conditions. Therefore, this transcutaneous hearing system seems to be an excellent alternative for patients who need a hearing solution for conductive hearing loss but for clinical reasons cannot undergo surgery or conventional hearing aids. Furthermore, it preserves skin over the mastoid and reduces the risk of infection. Otherwise it has benefits verified by absence of head pressure and improvement of patient's quality of life.